Graphene-based platforms for cancer therapeutics - Patel, Sunny C (Ther Deliv, 2016)
Graphene is a multifunctional carbon nanomaterial and could be utilized to develop platform technologies for cancer therapies. Its surface can be covalently and noncovalently functionalized with anticancer drugs and functional groups that target cancer cells and tissue to improve treatment efficacies. Furthermore, its physicochemical properties can be harnessed to facilitate stimulus responsive therapeutics and drug delivery. This review article summarizes the recent literature specifically focused on development of graphene technologies to treat cancer. We will focus on advances at the interface of graphene based drug/gene delivery, photothermal/photodynamic therapy and combinations of these techniques. We also discuss the current understanding in cytocompatibility and biocompatibility issues related to graphene formulations and their implications pertinent to clinical cancer management.